2011
DOI: 10.1007/s11095-011-0640-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Influence of Primary Crystallization Conditions on the Mechanical Properties and Secondary Processing Behaviour of Fluticasone Propionate for Carrier Based Dry Powder Inhaler Formulations

Abstract: Crystallisation conditions may affect the mechanical properties of FP, and therefore secondary processing of the material and their interfacial properties and product performance in carrier based DPI formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…6) appeared to be sensitive to shift in the balance of forces between FP and SX upon FP lagering. As has been indicated in a number of studies, the greater the adhesive tendency between FP and SX, the more significant is the improvement in aerosolization performance of SX (1,16,19). These studies proposed that higher deaggregation efficiency of the SX occurred as a result of the greater propensity of FP and SX to form fine particle agglomerates during blending.…”
Section: In Vitro Aerosolization Performance Of Binary Dpi Formulationsmentioning
confidence: 89%
See 2 more Smart Citations
“…6) appeared to be sensitive to shift in the balance of forces between FP and SX upon FP lagering. As has been indicated in a number of studies, the greater the adhesive tendency between FP and SX, the more significant is the improvement in aerosolization performance of SX (1,16,19). These studies proposed that higher deaggregation efficiency of the SX occurred as a result of the greater propensity of FP and SX to form fine particle agglomerates during blending.…”
Section: In Vitro Aerosolization Performance Of Binary Dpi Formulationsmentioning
confidence: 89%
“…al. (1). They also showed that different solvent and anti-solvent conditions during primary crystallization conditions could directly affect the interfacial surface chemistry of the secondary processed FP.…”
Section: Post-micronization Conditioning Effects On Interfacial Forcesmentioning
confidence: 98%
See 1 more Smart Citation
“…These data highlight the challenges faced during generic drug product development, particularly as in most cases, the API and excipient are procured through third-party channels. Our previous work has suggested that variation in particle size and interfacial properties may be related to the process history of the API (23). In particular, the elastic properties of primary FP crystals that are secondarily processed by air-jet micronization results in material that does not always meet particle size specification and has variable surface interfacial properties.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the elastic properties of primary FP crystals that are secondarily processed by air-jet micronization results in material that does not always meet particle size specification and has variable surface interfacial properties. This has been shown to impact finished drug product performance in both binary and combination DPI formulations (23). In order to understand the impact of the surface interfacial forces of the API on in vitro drug deposition, all batches of API were formulated with either milled or sieved lactose for further formulation investigation with the MOD MH 2 test device.…”
Section: Discussionmentioning
confidence: 99%